OPTIMASI SISTEM MATERIAL HANDLING KOMPONEN SHEET METAL MELALUI PENDEKATAN PRINSIP KARAKURI KAIZEN - Gilrandy Azalia Muntaz (2024)
Karakuri kaizen is a development principle in the world of manufacturing as a whole which has a very significant impact on the work flow of a company itself. In this research, an optimization of the material handling model will be carried out by approaching the karakuri kaizen principle on a conventional material handling tool. Optimization efforts are made by adding features to material handling tools to help workers maintain ergonomic posture when carrying out loading and unloading activities using trolleys. From the results of the assessment using the Rapid Entire Body Assessment (REBA) method, the potential ergonomic risk value for activities using conventional material handling models is 8 (high risk). Then through optimization using the karakuri kaizen principle approach, the optimal value according to the REBA method rules is divided into two categories, namely value 3 (low risk) for the optimal load category and value 4 (medium risk) for the actual load category. These results show that the application of karakuri kaizen can reduce potential ergonomic risks by changing the worker's body posture which becomes more stable when carrying out work activities and does not use additional energy in an effort to optimize the material handling model used.